The Chilean civil military dictatorship (1973-1990) as an affective experience in the educational context: didactic potentialities and challenges (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2023)
Research on the Chilean civil military dictatorship has scarcely considered emotions and their potentialities. Therefore, the objective of this article is to identify the didactic opportunities and challenges that arise when approaching the Chilean dictatorship as a difficult knowledge that provokes affectations. Thus, among the opportunities is the possibility of creating educational spaces where students can represent the questions and concerns they experience when encountering the testimonies of the past, in addition to being able to reflect on why they feel certain emotions. Together with this, this approach allows for reflection with students on the ethical demands of the past towards the present. On the other hand, the challenges are linked to teacher training, with their recognition as subjects who experience affectations and the need to reflect on how to incorporate uncertainty and diversity of learning in the classroom.
Keywords: Chilean civil military dictatorship; emotions; affectation; difficult knowledge; Didactics of History and Social Sciences